Reconfiguring the risk of financial organizations as a consequence of the green transition and a potential source of ‘Green Swan events’ - Smuda-Kocoń, Marlena (Journal of Management and Financial Sciences, 2025)
The green transition may have a significant impact on the risk reconfiguration at financial institutions, resulting in a redefinition of their existing role in the economy. Thus, the aim of the article is to identify the determinants of risk in the activities of financial institutions, resulting from the green transition, and to diagnose to what extent the new conditions may exert a modifying effect on the existing constellation of traditional risks in banks. Cognitively interesting questions emerge when the issue of ESG risk and its transmission channels is juxtaposed with the concept of the Talebian ‘Black Swan’. The question “To what extent is there a case to treat ESG risks as a potential source of so-called black swan events?” captures the point of the research problem. The results of the research carried out indicate that financial institutions are taking into account specific areas of risk as a result of the changing environment in which they operate. The constellation of traditional risks has changed. In addition, the ‘Green Swan’ metaphor may prove useful in explaining the mechanisms and repercussions associated with the green transition.